The birds of the marine shore of San Andres, Pisco, Ica : Birds of san andres - Pulido Capurro, Víctor (2025)
The marine shore of the San Andres beaches is located on the north of the Paracas National Reserve and on the west of the Peruvian Air Force Base and the Pisco International Airport in Ica. It presents a variety of habitats such as marine shores, rocky, stony, sandy, grassy and sea water surface. A total of 95 species were recorded, comprised of 12 orders and 26 families. Of the 95 species, 43 are resident, 38 are migratory from the Nearctic region, 3 from the Southern region, 2 from the Andes, one from the Galapagos, one vagrant and 7 occasional visitors. The most abundant species were Leocophaeus pipixcan and Chroicocephalus cirrocephalus gulls. These seashore habitats have biodiversity relevance because they are located within the northern boundary of the buffer zone of the Paracas National Reserve, and therefore as a protected natural area is internationally recognized as a Ramsar site. The objective is to inventory and quantify the most common bird species residing on the marine coastal shore and to evaluate the current conservation status of the San Andres beach habitats.